Spiritual Leadership: Theory and Practices in Schools (a Literature Review) - Hariri, Hasan; Fadhila Bumay, Anitia; Rusdiani, Atik; Sucitra, Diah Ayu (Universitas Ahmad Dahlan, 2025)
Literature reviews on spiritual leadership lack research, particularly those conducted in the school context between 2020 and 2024. This article explores and reviews the theory and practices of spiritual leadership in schools. The articles used in this literature review were obtained through Google Scholar by entering the keywords